Bacteriological profile with antibiotic sensitivity pattern of burn wound infections in a peripheral tertiary care hospital - Mandal, Arnab; Das, Swapan (International Surgery Journal, 2021)
Background: India, has an estimated burn incidence of 6-7 million annually. Nearly 10% of these are life threatening and require hospitalization, and main cause of mortality and morbidity of these burn patients were wound infection and sepsis after 1st 24 hours. The present study was tried to determine specific pattern of burn wound infections, and antibiotic susceptibility of those isolates. Methods: After matching inclusion and exclusion criteria, total 55 patients were taken for this institution based, prospective observational study. Wound swabs were collected on day 7 and cultured aerobically in MacConkey agar and 5% blood agar and antibiotic susceptibility testing was done on Muller Hinton agar using Kirby-Bauer disc diffusion method. Results: Among study population 69.1% patients were female and majority (29.1%) of the patients belongs to age group from 21 to 30. It was found that 48 wound swabs were positive for microorganisms, of which Pseudomonas aeruginosa was most common isolated organism (23.6%), followed by Klebsiella pneumoniae (16.4%) and Staphylococcus aureus (14.5%). The most effective antibiotic found in this study was piperacillin/tazobactam, followed by imipenem/cilastatin. Conclusions: It was seen that gram-negative organisms were more prevalent. Pseudomonas aeruginosa was the most common microorganism and piperacillin/tazobactam was most effective antibiotic.